2017
DOI: 10.1080/10872981.2017.1272838
|View full text |Cite
|
Sign up to set email alerts
|

Learning health ‘safety’ within non-technical skills interprofessional simulation education: a qualitative study

Abstract: Background: Healthcare increasingly recognises and focusses on the phenomena of ‘safe practice’ and ‘patient safety.’ Success with non-technical skills (NTS) training in other industries has led to widespread transposition to healthcare education, with communication and teamwork skills central to NTS frameworks. Objective: This study set out to identify how the context of interprofessional simulation learning influences NTS acquisition and development of ‘safety’ amongst learners. Methods: Participants receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Simulated wards and clinics have also been employed as part of a larger programme in the urology-focussed course by Khan et al [21], using the 'SimMan' model, and for general NTS training with multiprofessional groups. These courses were all well received [21,22]. Future courses could stand to gain from incorporating these ideas into a mixed curriculum comprising both OR and ward scenarios.…”
Section: Crisis Resource Management and Ward-based Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulated wards and clinics have also been employed as part of a larger programme in the urology-focussed course by Khan et al [21], using the 'SimMan' model, and for general NTS training with multiprofessional groups. These courses were all well received [21,22]. Future courses could stand to gain from incorporating these ideas into a mixed curriculum comprising both OR and ward scenarios.…”
Section: Crisis Resource Management and Ward-based Scenariosmentioning
confidence: 99%
“…Team training rather than individual training has been found useful by trainees, particularly for communication skills [25]. Interprofessional team working needs to be addressed to improve patient safety, involving the range of professions that compose an OR team benefits simulations by improving communication and decreasing anxiety between groups [22,26,27]. This effect is most relevant to junior trainees, but seniors should also be aware of the issues faced by the less senior staff in their teams [22].…”
Section: Team Trainingmentioning
confidence: 99%
“…All nursing staff (36) who participated in the workshop (actively participated in the simulation scenario or/and observed) were invited by the nurse manager to participate in a focus-group interview. For practical reasons the participants were invited to focus-group interviews on the same day as they had a one-day course at work, on three different days.…”
Section: Participants and Data Collectionmentioning
confidence: 99%
“…Attention has also been given to how this emerging expertise is acquired in clinical environments, with distinctions made between technical and nontechnical skills (NTS) and how these capabilities are developed (Forsberg, Ziegert, Hult, & Fors, ; Herron et al., ; Johnsen, Fossum, Vivekananda‐Schmidt, Fruhling, & Slettebø, ). The nontechnical skills involved in CDM have been defined as the cognitive and interpersonal skills that complement technical knowledge in support of safe, effective and efficient care (Gordon, Fell, Box, Farrell, & Stewart, ). Earlier research identified the main skill categories of surgeon's nontechnical skills were communication, teamwork, leadership and decision‐making (Yule, Flin, Paterson‐Brown, & Maran, ).…”
Section: Introductionmentioning
confidence: 99%